High-strength nano-modified dental restorative material and preparation method thereof
By using phosphate derivative-modified polyvinyl alcohol as a binder to bond with nano-zirconia ceramics, the interfacial crosslinking ability of zirconia-based resin-infiltrated ceramic network composite materials is enhanced, solving the problem of insufficient mechanical properties in dental restorations and achieving higher strength and toughness.
Patent Information
- Application Number
- CN202510188097.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-02-20
AI Technical Summary
Existing zirconia-based resin-infiltrated ceramic network composite materials have problems in dental restorations, such as insufficient interfacial bonding between the ceramic phase and the infiltrated resin phase, resulting in low flexural strength and fracture toughness.
A high-strength nano-modified dental restorative material was prepared by using phosphate derivative-modified polyvinyl alcohol as a binder, combined with nano-zirconia ceramics, polyoxymethylene resin and inorganic fillers, and enhancing the adhesion between the components through covalent bonds and polymerization reactions.
It significantly improves the flexural strength, flexural modulus, hardness and fracture toughness of dental restorative materials, thus broadening their application in dental restoration.
Smart Images

Figure BDA0005279153450000041 
Figure BDA0005279153450000051 
Figure BDA0005279153450000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dental restoration materials, specifically relating to a high-strength nano-modified dental restoration material and its preparation method. Background Technology
[0002] Dental restorative materials can be categorized based on their composition into metal materials, all-ceramic materials, and resin materials. Traditional metal materials offer good compressive strength, resisting chewing pressure, and are relatively inexpensive, often requiring only a single treatment session. However, they are less aesthetically pleasing and may require significant tooth tissue removal, leading to their gradual replacement by newer materials. All-ceramic materials, due to their excellent aesthetics and biocompatibility, have become a common restorative material on the market. However, their brittleness, the need for sintering during crystallization and glazing, the special treatment required for bonding, and the significant wear on teeth are all undeniable problems. Resin materials possess good aesthetics and processing properties, particularly their excellent bonding and tooth-like physical properties, which have garnered considerable attention. However, defects such as polymerization shrinkage and poor wear resistance limit their further application in dental restorations.
[0003] Resin-infiltrated ceramic network composites are obtained by infiltrating a pre-sintered ceramic scaffold network with organic monomers and then polymerizing it at high temperatures. These composites exhibit superior mechanical properties compared to traditional composite resins, and their elastic modulus is closer to that of dentin, making them a significant advantage as dental restorative materials. Zirconia-based ceramics have recently been considered a promising scaffold material for polymer-infiltrated ceramic networks. Zirconia-based resin-infiltrated ceramic network composites exhibit higher flexural modulus and Vickers hardness, but they suffer from insufficient interfacial bonding between the ceramic phase and the infiltrated resin phase, resulting in lower flexural strength and fracture toughness. Enhancing the interfacial cross-linking ability between the components in these materials, and thus developing zirconia-based resin-infiltrated ceramic network composites with superior mechanical properties to broaden their application in dental restorations, is a pressing issue that needs to be addressed. Summary of the Invention
[0004] The purpose of this invention is to provide a high-strength nano-modified dental restorative material and its preparation method, so as to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: On one hand, the present invention provides a high-strength nano-modified dental restoration material, wherein the raw materials for preparing the high-strength nano-modified dental restoration material, by weight, include 35-70g of polyoxymethylene resin, 20-50g of nano-zirconia ceramic, 2-5g of coupling agent, 1-5g of adhesive and 2-8g of inorganic filler, wherein the adhesive is polyvinyl alcohol modified with phosphate derivative.
[0006] As a further improvement, the raw materials for preparing the phosphoric acid derivative modified polyvinyl alcohol include polyvinyl alcohol and 2-phosphobutane-1,2,4-tricarboxylic acid, wherein the mass ratio of polyvinyl alcohol to 2-phosphobutane-1,2,4-tricarboxylic acid is 1:(2-6).
[0007] As a further improvement, the preparation method of the phosphoric acid derivative modified polyvinyl alcohol includes the following steps: dissolving polyvinyl alcohol in deionized water, stirring at 90-100℃ for 1-2 hours to obtain a reaction solution, adjusting the pH of the reaction solution to 1-3, adding 2-phosphobutane-1,2,4-tricarboxylic acid to the reaction solution, stirring at 45-50℃ for 1-5 hours, and post-processing to obtain phosphoric acid derivative modified polyvinyl alcohol, wherein the CAS number of 2-phosphobutane-1,2,4-tricarboxylic acid is 37971-36-1.
[0008] As a further improvement, the raw materials for preparing the nano-zirconia ceramic include zirconium oxychloride, yttrium oxide, aluminum nitrate, and sodium hydroxide.
[0009] As a further improvement, the preparation method of the nano-zirconia ceramic includes the following steps:
[0010] S5-1, using anhydrous ethanol as a solvent, prepare a zirconium oxychloride solution with a concentration of 0.1-0.4 mol / L, then add yttrium oxide and aluminum nitrate to form reaction solution A; using deionized water as a solvent, prepare a sodium hydroxide solution and add a dispersant to form reaction solution B;
[0011] S5-2, place reaction solution B in a constant temperature heating magnetic stirrer, control the temperature at 50-60℃, control the stirring speed at 500-800r / min, add reaction solution A dropwise to reaction solution B at a uniform rate, let stand and age for 30-60min after the reaction is completed, and wash the obtained precipitate 5-10 times with deionized water and ethanol.
[0012] S5-3, the precipitate washed in step S5-2 is placed in an oven at 80-100℃ and dried for 8-12 hours to obtain a zirconia precursor. The zirconia precursor is then ground and calcined to obtain nano-zirconia ceramics.
[0013] As a further improvement, the concentration of sodium hydroxide solution in step S5-1 is 0.2-0.8 mol / L, and the dispersant comprises one or more of PEG400, PEG1000 and PEG2000.
[0014] As a further improvement, the calcination temperature in step S5-3 is 300-500℃, and the calcination time is 1-5h.
[0015] As a further improvement, the coupling agent comprises a silane coupling agent, a titanate coupling agent, and a phosphate coupling agent, wherein the silane coupling agent comprises one or more of KH550, KH560, and KH570.
[0016] As a further improvement, the inorganic filler comprises one or more of nano-zirconia particles, nano-alumina particles, and sodium aluminum silicate.
[0017] On the other hand, the present invention provides a method for preparing a high-strength nano-modified dental restorative material, comprising the following steps:
[0018] S10-1, Weigh the adhesive and acetone, add them to a beaker and mix and stir. Continue heating and stirring at 40-50℃ until the adhesive is completely dissolved. Cool to room temperature to obtain an adhesive solution with a concentration of 0.1-0.5mol / L.
[0019] S10-2, deionized water, ethanol and coupling agent are mixed and stirred to form a modification solution and the pH of the modification solution is adjusted to 3-4. The nano-zirconia ceramic is immersed in the modification solution and vacuum-assisted for 5-6 hours, followed by vacuum drying for 3-4 hours to obtain modified nano-zirconia ceramic.
[0020] S10-3, The adhesive solution obtained in step S10-1 and the modified nano-zirconia ceramic obtained in step S10-2 are placed in a vacuum dryer, and polyoxymethylene resin and inorganic filler are added at the same time. The vacuum is repeatedly drawn to obtain the ceramic after resin infiltration. The ceramic after resin infiltration is then heat-cured at 80-100℃ for 8-12 hours to obtain a high-strength nano-modified dental restoration material.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention provides a high-strength nano-modified dental restorative material, which uses polyvinyl alcohol modified with phosphate derivatives as a binder. This type of binder has both carboxylic acid functional groups and phosphate functional groups, which can form covalent bonds with the ceramic phase and undergo polymerization reactions with the resin phase, thereby promoting the adhesion between the components and further enhancing the mechanical properties of the resin-permeable ceramic composed of polyoxymethylene resin as the resin phase and nano-zirconia ceramic as the ceramic phase. Detailed Implementation
[0022] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.
[0023] In the following examples, the monomers and related reagents used were all commercially available. The polyoxymethylene resin was purchased from Jiangsu Bost Chemical Technology Co., Ltd.; PEG400 was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; polyvinyl alcohol was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; and commercially available nano-zirconia ceramics were purchased from Shanghai Liantian Materials Technology Co., Ltd., with the product number LT-ZrO2-006-2.
[0024] The following examples and comparative examples all include the following steps:
[0025] Preparation of adhesives:
[0026] Weigh each component and its content according to Table 1, dissolve polyvinyl alcohol in deionized water, stir at 90°C for 2 hours to obtain a reaction solution, adjust the pH of the reaction solution to 1, add 2-phosphobutane-1,2,4-tricarboxylic acid to the reaction solution, stir at 45°C for 3 hours, evaporate the solvent, and obtain polyvinyl alcohol modified with phosphate derivative.
[0027] The combinations and contents of the adhesives used in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.
[0028] Table 1
[0029]
[0030]
[0031] Preparation of nano-zirconia ceramics:
[0032] In step S5-1, zirconium oxychloride is added to anhydrous ethanol as a solvent to prepare 5 mL of a 0.2 mol / L zirconium oxychloride solution. Then, 50 mg of yttrium oxide and 50 mg of aluminum nitrate are added to form reaction solution A. In deionized water as a solvent, 5 mL of a 0.4 mol / L sodium hydroxide solution is prepared, and 10 mg of PEG400 dispersant is added to form reaction solution B.
[0033] Step S5-2: Place reaction solution B in a constant temperature heating magnetic stirrer, control the temperature at 55℃ and the stirring speed at 600r / min, add reaction solution A dropwise to reaction solution B at a uniform rate, let stand and age for 60min after the reaction is completed, and wash the precipitate five times each with deionized water and ethanol.
[0034] Step S5-3: Place the precipitate washed in step S5-2 in an oven at 85°C and dry it for 8 hours to obtain a zirconia precursor. Then grind the zirconia precursor and calcine it at 500°C for 4 hours to obtain nano-zirconia ceramics.
[0035] The preparation methods of the high-strength nano-modified dental restorative materials of Examples 1-7 and Comparative Example 1 include the following steps:
[0036] Step S10-1: Weigh the acetone and adhesive and add them to a beaker and mix and stir. Continue heating and stirring at 45°C until the adhesive is completely dissolved. Cool to room temperature to obtain an adhesive solution with a concentration of 0.2 mol / L.
[0037] Step S10-2: Deionized water, ethanol and coupling agent are mixed and stirred in a mass ratio of 15:15:1 to form a modification solution. The pH of the modification solution is adjusted to 3. The nano-zirconia ceramic is immersed in the modification solution. Under vacuum assistance, it is immersed for 5 hours and then vacuum dried for 3 hours to obtain the modified nano-zirconia ceramic.
[0038] In step S10-3, the adhesive solution obtained in step S10-1 and the modified nano-zirconia ceramic obtained in step S10-2 are placed in a vacuum dryer, and polyoxymethylene resin and inorganic filler are added at the same time. The vacuum is repeatedly drawn 3 times to obtain the ceramic after resin infiltration. The ceramic after resin infiltration is then heat-cured at 100℃ for 8 hours to obtain a high-strength nano-modified dental restoration material.
[0039] Example 1 provides a high-strength nano-modified dental restorative material, comprising 50g of polyoxymethylene resin, 50g of nano-zirconia ceramic, 2g of coupling agent (KH550 silane coupling agent), 2g of adhesive (adhesive A) and 2g of inorganic filler (nano-zirconia particles).
[0040] Example 2 provides a high-strength nano-modified dental restoration material, comprising 65g of polyoxymethylene resin, 40g of nano-zirconia ceramic, 5g of coupling agent (KH560 silane coupling agent), 5g of adhesive (adhesive B), and 5g of inorganic filler (sodium aluminum silicate).
[0041] Example 3 provides a high-strength nano-modified dental restorative material, comprising 70g of polyoxymethylene resin, 30g of nano-zirconia ceramic, 5g of coupling agent (KH570 silane coupling agent), 4g of adhesive (adhesive C), and 8g of inorganic filler (nano-alumina particles).
[0042] Example 4 provides a high-strength nano-modified dental restorative material with a composition that is basically the same as that in Example 1, except that 2g of adhesive A is replaced with 2g of adhesive D.
[0043] Example 5 provides a high-strength nano-modified dental restorative material with a composition that is basically the same as that in Example 1, except that 2g of adhesive A is replaced with 2g of adhesive E.
[0044] The composition and quality of the high-strength nano-modified dental restorative material provided in Comparative Example 1 are basically the same as those in Example 1, except that 2g of adhesive A is replaced with 10g of adhesive A.
[0045] The composition and quality of the high-strength nano-modified dental restorative material provided in Comparative Example 2 are basically the same as those in Example 1, except that 2g of adhesive A is replaced with 0.5g of adhesive A.
[0046] The composition of a high-strength nano-modified dental restorative material provided in Comparative Example 3 is basically the same as that in Example 1, except that 2g of adhesive A is replaced with 2g of polyvinyl alcohol.
[0047] The composition of a high-strength nano-modified dental restorative material provided in Comparative Example 4 is basically the same as that in Example 1, except that 50g of nano-zirconia ceramic is replaced with 50g of commercially available nano-zirconia ceramic.
[0048] The testing method is as follows:
[0049] According to the standard GB 30367-2013 for dental ceramic materials, the high-strength nano-modified dental restorative materials prepared in Examples 1-5 and Comparative Examples 1-4 were prepared into 35mm×4mm×3mm strips, which were then chamfered, polished, and tested for flexural strength and flexural modulus by a three-point bending test.
[0050] The high-strength nano-modified dental restorative materials obtained in Examples 1-5 and Comparative Examples 1-4 were prepared into smooth samples of 2mm × 2mm × 2mm, and the hardness of the samples was measured by a Vickers hardness tester.
[0051] The high-strength nano-modified dental restorative materials prepared in Examples 1-5 and Comparative Examples 1-4 were made into 44mm×4mm×3mm strips. After polishing and cutting out V-groove notches with a depth of 1mm and a width of 2mm, the fracture toughness of the samples was tested using a universal tensile testing machine.
[0052] The test results are shown in Table 2, as follows:
[0053] Table 2
[0054]
[0055]
[0056] Examples 1-3 show that the high-strength nano-modified dental restorative material provided by the present invention is composed of polyoxymethylene resin, nano-zirconia ceramic, coupling agent, binder, and inorganic filler, and possesses excellent flexural strength, flexural modulus, hardness, and fracture toughness. Polyoxymethylene resin serves as the resin phase, nano-zirconia ceramic as the ceramic phase, and polyvinyl alcohol modified with phosphate derivatives provided by the present invention is used as the binder, forming a resin-permeable ceramic network, thereby improving the mechanical properties of this type of dental restorative material.
[0057] A comparison of Examples 4-5 and Example 1 shows that the high-strength nano-modified dental repair material provided by the present invention exhibits superior flexural strength, flexural modulus, hardness, and fracture toughness when the mass ratio of polyvinyl alcohol to phosphate derivative is within a suitable range.
[0058] Comparing Comparative Examples 1-2 with Example 1, it can be seen that when the adhesive content is within a suitable range, the high-strength nano-modified dental restorative material prepared by the preparation method provided by the present invention has superior flexural strength, flexural modulus, hardness and fracture toughness.
[0059] Comparing Comparative Examples 3-4 and Example 1, it can be seen that using the phosphate derivative-modified polyvinyl alcohol provided by the present invention as an adhesive, and simultaneously using the nano-zirconia ceramic provided by the present invention, makes this type of adhesive have carboxylic acid functional groups and phosphate functional groups. It can not only combine with oxygen atoms on the surface of nano-zirconia ceramic to remove water molecules and form covalent bonds, but also undergo a polymerization reaction with the resin phase to further enhance the adhesion, promote the interfacial compatibility of each component, and enhance the flexural strength, flexural modulus, hardness and fracture toughness of the overall dental restorative material.
[0060] In summary, the present invention provides a high-strength nano-modified dental restorative material, which is prepared by using polyoxymethylene resin as the resin phase, nano-zirconia ceramic as the ceramic phase, and phosphate derivative-modified polyvinyl alcohol as the binder, with the addition of a small amount of inorganic filler and coupling agent. This type of phosphate derivative-modified polyvinyl alcohol can form covalent bonds with the ceramic phase and undergo polymerization reaction with the resin phase, further improving the adhesion between the components, thereby enhancing the flexural strength, flexural modulus, hardness and fracture toughness of this type of dental restorative material.
[0061] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it. They should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A high-strength nano-modified dental restorative material, characterized in that, The raw materials for preparing the high-strength nano-modified dental restorative material, by weight, include 35-70g of polyoxymethylene resin, 20-50g of nano-zirconia ceramic, 2-5g of coupling agent, 1-5g of adhesive and 2-8g of inorganic filler, wherein the adhesive is polyvinyl alcohol modified with phosphate derivative. The raw materials for preparing the phosphate derivative modified polyvinyl alcohol include polyvinyl alcohol and 2-phosphobutane-1,2,4-tricarboxylic acid, wherein the mass ratio of polyvinyl alcohol to 2-phosphobutane-1,2,4-tricarboxylic acid is 1:(2-6). The preparation method of the phosphoric acid derivative modified polyvinyl alcohol includes the following steps: dissolving polyvinyl alcohol in deionized water, stirring at 90-100℃ for 1-2h to obtain a reaction solution, adjusting the pH of the reaction solution to 1-3, adding 2-phosphobutane-1,2,4-tricarboxylic acid to the reaction solution, stirring at 45-50℃ for 1-5h, and then performing post-treatment to obtain phosphoric acid derivative modified polyvinyl alcohol. The raw materials for preparing the nano-zirconia ceramics include zirconium oxychloride, yttrium oxide, aluminum nitrate, and sodium hydroxide. The preparation method of the nano-zirconia ceramic includes the following steps: S5-1, using anhydrous ethanol as a solvent, prepare a zirconium oxychloride solution with a concentration of 0.1-0.4 mol / L, then add yttrium oxide and aluminum nitrate to form reaction solution A; using deionized water as a solvent, prepare a sodium hydroxide solution and add a dispersant to form reaction solution B; S5-2, place reaction solution B in a constant temperature heating magnetic stirrer, control the temperature at 50-60℃, control the stirring speed at 500-800 r / min, add reaction solution A dropwise to reaction solution B at a uniform rate, let stand and age for 30-60 min after the reaction is completed, and wash the obtained precipitate 5-10 times with deionized water and ethanol. S5-3, the precipitate washed in step S5-2 is placed in an oven at 80-100℃ and dried for 8-12 hours to obtain a zirconia precursor. The zirconia precursor is then ground and calcined to obtain nano-zirconia ceramics.
2. The high-strength nano-modified dental restorative material according to claim 1, characterized in that, In step S5-1, the concentration of sodium hydroxide solution is 0.2-0.8 mol / L, and the dispersant contains one or more of PEG400, PEG1000 and PEG2000.
3. The high-strength nano-modified dental restorative material according to claim 1, characterized in that, In step S5-3, the calcination temperature is 300-500℃ and the calcination time is 1-5h.
4. The high-strength nano-modified dental restorative material according to claim 1, characterized in that, The coupling agent comprises silane coupling agent, titanate coupling agent and phosphate coupling agent, wherein the silane coupling agent comprises one or more of KH550, KH560 and KH570.
5. The high-strength nano-modified dental restorative material according to claim 1, characterized in that, The inorganic filler comprises one or more of nano-zirconia particles, nano-alumina particles, and sodium aluminum silicate.
6. A method for preparing a high-strength nano-modified dental restorative material according to any one of claims 1-5, characterized in that, Includes the following steps: S10-1, Weigh the adhesive and acetone, add them to a beaker and mix and stir. Continue heating and stirring at 40-50℃ until the adhesive is completely dissolved. Cool to room temperature to obtain an adhesive solution with a concentration of 0.1-0.5mol / L. S10-2, deionized water, ethanol and coupling agent are mixed and stirred to form a modification solution and the pH of the modification solution is adjusted to 3-4. The nano-zirconia ceramic is immersed in the modification solution and vacuum-assisted for 5-6 hours, followed by vacuum drying for 3-4 hours to obtain modified nano-zirconia ceramic. S10-3, the adhesive solution obtained in step S10-1 and the modified nano-zirconia ceramic obtained in step S10-2 are placed in a vacuum dryer, and polyoxymethylene resin and inorganic filler are added at the same time. The vacuum is repeatedly drawn to obtain the ceramic after resin infiltration. The ceramic after resin infiltration is then heat-cured at 80-100℃ for 8-12 hours to obtain a high-strength nano-modified dental restoration material.
Citation Information
Patent Citations
False tooth with high wear resistance and acid etching resistance and processing method thereof
CN117430416A
